Synthesis, Characterization, and Antioxidant Activity of a New Copper(II)-imidazole Derivative Complex - Colaço de Oliveira , Ariel; Pedrozo da Silva , Ana Claudia; Gustavo Sampaio de Oliveira FIlho, Antônio; Tatiani Dusman Tonin, Lilian; Luiz Tessaro, André; Nicolussi Pereira , Felipe; de Arruda Leite Júnior, Jonas; Block Samulewski, Rafael (Orbital: The Electronic Journal of Chemistry, 2025)
Degenerative diseases such as cancer, cataract, and cerebral dysfunction are increasingly associated with free radicals. Copper(II) complexes exhibit antioxidant activity and can act in the treatment of these diseases altering or inhibiting cellular functions by intercalations with nitrogenous bases of DNA. Those complexes can be employed in the development of new drugs and materials for the treatment of these diseases or as preventive agents. In this work, we present the synthesis and characterization of a complex formed by an imidazole-type ligand and copper(II). NMR data confirm the structure of ligand and that its interaction with copper(II) ions produces the complex [Cu(3NIMDZ-H)(OH2)5](ClO4)2 with a coordinated binding between copper(II) ion and nitrogen of the imidazole ring. Density functional theory (DFT) calculations performed at the B3LYP-D3(BJ)/def2-SVP level of theory for both the complex and ligand reveal that the formation of the complex is spontaneous, exhibiting a copper-nitrogen bond length of 1.988 Å. The antioxidant assays showed a high-speed inhibition of complex radicals regarding free ligand. IC50 value is 1.5 times higher than the BHT standard, demonstrating the high antioxidant power of this compound. [Cu(3NIMDZ-H)(OH2)5]2+  shows a fast kinetics behavior for DPPH inhibition, which shows the possibility of new material application in antitumoral drug development.